Manajemen Kecemasan pada Pasien yang Menjalani Pembedahan Jantung - Bambang Aditya Nugraha; Sandra Pebrianti; Hesti Platini; Gusgus Ghraha Ramdhanie (Jurnal Medika Cendikia, 2019)
Anxiety is a problem that found in patients with heart disease. Anxiety will increase when the patient has to undergo the cardiac surgery procedure. Anxiety management must be conducted to prevent postoperative hemodynamic instability and neurohormonal deterioration. Thus it becomes important to formulate the anxiety management to improving the recovery process after surgery and patients quality of life of. The purpose of this literature review is to identify anxiety management on cardiac surgery patient. The search method uses Google Scholar databases using inclusion criteria proposed in consideration management that support heart surgery procedures, the year of publication between 2010-2020, containing the full article, in bahasa and english. Search results found 62 articles, 27 met the criteria of the year and 13 represented the complete article. And finally found as many as 6 articles that match the focus of the search. There are to type anxiety management e.g educational supportive and relaxation technique. Relaxation and supportive educative technique interventions can be used to manage anxiety to improve the post-surgical recovery process and quality of life.